Sport-specific differences in vertical jump force-time metrics between professional female volleyball, basketball, and handball players - Cabarkapa, D. V.; Cabarkapa, D.; Aleksic, J.; Fry, A. C. (The Journal of Strength and Conditioning Research, 2025)
The purpose of the present study was to examine the sport-specific differences in countermovement vertical jump (CMJ) force-time metrics among professional female volleyball, basketball, and handball players. Ninety-four athletes volunteered to participate in the present study (i.e., 41 volleyball, 20 basketball, and 33 handball). After a brief warm-up procedure, each athlete performed 3 nonconsecutive CMJs while standing on a force plate system sampling at 1,000 Hz. Nineteen force-time metrics were selected for performance analysis purposes, including both eccentric and concentric phases of the jumping motion. A one-way analysis of variance with Tukey post-hoc comparisons was used to examine statistically significant differences in each dependent variable across 3 sports (p < 0.05). The results reveal that volleyball athletes demonstrate significantly greater impulse, velocity, and mean and peak power during the eccentric phase of the CMJ compared with both basketball and handball players, and longer eccentric duration than basketball players. During the concentric phase, volleyball athletes showed significantly greater duration, impulse, and velocity compared to their handball and basketball counterparts, with higher mean and peak force observed only in comparison with basketball players. In addition, volleyball athletes had significantly greater jump height and deeper countermovement depth than the other 2 groups. However, the difference in reactive strength index-modified was detected only between the handball and volleyball athletes, with volleyball players exhibiting greater values. Overall, these findings can help sports practitioners with the development of specialized performance-enhancement training programs for athletes competing in sports such as basketball, volleyball, and handball.